Penataan Kawasan Semanggi Surakarta Sebagai Kampung Ramah Anak - Hardiyanto, Arlis, Ir. Alpha Febela Priyatmono, MT, Wisnu Setiawan ST., M.Arch, Ph.D (2016)
High urbanization rate in urban areas resulted in the availability of land for shelter is limited. One of the areas in Surakarta which has slum is a village Semanggi. By mapping potential slum area can be used as a reference for the development and management of the region's quality improvement. Development of settlement areas as child-friendly village should pay attention to the condition of the user (especially children). The purpose of this report is to create Region Semanggi Surakarta as a village, targeting friendly approach towards children (specification components decent location is the provision of social facilities (health and education). The potential development area of Semanggi Surakarta was divided into a development area of Ring I Subsector AD, with each potential that can be developed. analysis and concept approach is divided into two, namely the analysis and the concept of the macro, and the analysis and the concept of micro divided into sub-chapters for more detail and thorough in the analysis process. the process of analysis conducted to support the planning and design of the village child-friendly.